Partial revision of freshwater shrimps from Central Sulawesi, Indonesia, with descriptions of two new species (Crustacea: Decapoda: Atyidae) - Cai, Yixiong; Wowor, Daisy; Choy, Satish (Zootaxa, 2009)
The taxonomy of freshwater shrimps of the family Atyidae from the Malili lake system, Central Sulawesi, is partially revised based on museum materials and fresh collections. Caridina lanceolata, C. masapi, C. spinata and C. loehae are redescribed and neotypes are designated as all type materials for these species are no longer extant. Two new species, C. woltereckae and C. mahalona, are described and illustrated in details.